Методичні підходи до оцінки кредитоспроможності позичальників - Фридинський, Валерій Олександрович; Потолова, Я. Ю. (НТУ "ХПІ", 2014)
Пропонується аналіз основних проблем та методів оцінки кредитоспроможності позичальників. Були представлені основні методи оцінки кредитоспроможності та визначені їх недоліки і переваги. Було визначено місце поняття «кредитоспроможність» у сфері надання кредитних послуг банками. У статті проаналізовано методичні підходи до оцінки кредитоспроможності з урахуванням галузевих особливостей, а саме підприємств торгівлі, оскільки ця галузь знаходиться на одному із перших місць за залученням кредитних ресурсів. Удосконалено методику оцінки кредитоспроможності торговельного підприємства на основі інтегрально-рейтингових показників, що враховує специфіку торговельної галузі та підвищить ефективність прийняття кредитних рішень. Результати дослідження можуть бути використані в практичній діяльності банківських установ.

An analysis of the basic problems and methods of assessing the creditworthiness of borrowers. Presented the main methods of assessment of creditworthiness and identify their advantages and disadvantages. It was determined the place of the concept of "creditworthiness" in the provision of credit services by the banks. The article analyzes methodological approaches to the assessment of creditworthiness, taking into account industry specifics. Improved methods of assessing the creditworthiness of commercial enterprise on the basis of the integrated rating, taking into account the specifics of the trading industry and increase the effectiveness of making credit decisions. The results of the study can be used in the practical activities of banking institutions. The analysis allows to conclude that the evaluation of the borrowers ' creditworthiness plays an important role, both for the banking institution and the borrower. The purpose of evaluating the creditworthiness of the borrower for the banking institution is avoid credit risk from non-repayment of loan. For the borrower the loan on the most favorable terms. Analyzed and systematized methods in varying degrees, are applied in the Ukrainian banking practice, and focus on their effective use in real conditions creditsepisode activity of enterprises and organizations.
Methodological approaches to assessing the creditworthiness of borrowers
Keywords: кредитування; платоспроможність; фінансові коефіцієнти; прогнозування; кредитні ризики; solvency; financial ratios; forecasting; credit risk